2011
DOI: 10.1073/pnas.1010933108
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the DNA polymerase B-proliferating cell nuclear antigen (PCNA)-DNA ternary complex

Abstract: DNA replication in archaea and eukaryotes is executed by family B DNA polymerases, which exhibit full activity when complexed with the DNA clamp, proliferating cell nuclear antigen (PCNA). This replication enzyme consists of the polymerase and exonuclease moieties responsible for DNA synthesis and editing (proofreading), respectively. Because of the editing activity, this enzyme ensures the high fidelity of DNA replication. However, it remains unclear how the PCNA-complexed enzyme temporally switches between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 33 publications
7
64
0
Order By: Relevance
“…The fully assembled Okazakisome (Figures 2 and 3) exhibits features compatible with previous EM studies of related subassemblies (PCNA-Lig-DNA [5] and PCNA-Pol-DNA [12]). To glean insight into the mechanism by which PCNA co-ordinates three client proteins to process Okazaki fragments, we fitted each constituent of the assembly using Chimera, based on their volumes and shapes (Figure 3).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…The fully assembled Okazakisome (Figures 2 and 3) exhibits features compatible with previous EM studies of related subassemblies (PCNA-Lig-DNA [5] and PCNA-Pol-DNA [12]). To glean insight into the mechanism by which PCNA co-ordinates three client proteins to process Okazaki fragments, we fitted each constituent of the assembly using Chimera, based on their volumes and shapes (Figure 3).…”
Section: Resultssupporting
confidence: 84%
“…1S5J fits extremely well in the density connecting PCNA2 and PCNA3 (Figure 3), forming two extensive contacts with the PCNA ring, consistent with the EM analysis of the PCNA-polymerase complex loaded on DNA [12].…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Because further extension of the DNA would sterically clash with the ring, such a large tilting angle appears unlikely in this case (41). EM analysis of PCNA/Pol-B/DNA and PCNA/ligase/DNA assemblies suggested that DNA was tilted by 13°and 16°, respectively (42,43). By contrast, in the replication factor C/ PCNA/DNA ternary assembly, the DNA axis was found to be nearly perpendicular to the PCNA ring (44).…”
Section: Structural Determinants Of Flexibility For the Ternary Assemmentioning
confidence: 89%